Factors Influencing Patients’ Intention to Bypass to Higher-Level Hospitals in Northern Vietnam - Tuan, Pham Van (International Journal of Psychosocial Rehabilitation, 2020)
Patients (bypassing to higher level hospital) tend to bypass nearby hospitals then selftransfer to higher-hospitals in recent years which causes hospital overcrowding. There is a huge impact on financial costs, time as well as the risk of cross-infection in hospitals, on drug resistance during treatment later. At the same time, it affects the management and payment of hospital fees of Vietnam Social Insurance.Quantitative research was conducted on stratified randomized samples of 315 patients in the Northern provinces from November 2019 to February 2020. The survey mainly takes place in populous provinces. The questionnaire was developed to collect data on patient characteristics, the impact of the reference group on perceptions and attitudes, the reasons leading to overtaking. In addition, interviews with a group of behavioral experts and leading medical doctors in Vietnam. The authors used SPSS software to analyze the EFA discovery factor and AMOS 22.0 software to analyze the CFA affirmation factor. The results of the study show that the factors of Hospital, Reference group, Awareness and Attitude positively impacted the intention to bypass to higher level hospital; in which attitude had the most positive impact (0.332) and Reference group had less impact than the other three factors (0.249). In addition, the Reference Group has a positive influence on Awareness (0.295) and Attitude (0.177). The research gap of the topic is to consider the influence of the reference group on attitudes and behaviors bypassing to higher level hospital of patients in Northern Vietnam.